Effectiveness of Bintaro Seeds Extract (Cerbera odollam Gaertn.) on Armyworm (Spodoptera litura (Fabricius) Mortality - Mery Sintia Dewi; Wachju Subchan; Jekti Prihatin (BIOEDUKASI, 2018)
Armyworm (Spodoptera litura (Fabricius) often lead to decreased productivity and even crop failures by causing leaves, fruits, and vegetables to become torn, cut, and punctured. Crop insecticides are an alternative to eradicating armyworm (Spodoptera litura (Fabricius). One plant that can be used as a vegetable insecticide is bintaro (Cerbera odollam Gaertn.) The bintaro plant (Cerbera odollam Gaertn.) has cerberin content that contribute to insect mortality. This study aims to determine the effectiveness of extract (Cerbera odollam Gaertn.) on mortality of armywork (Spodoptera litura (Fabricius). This study was a type of experiment using Completely Randomized Design (CRD) with five treatments and one control. The results showed that the effectiveness of seeds bintaro extract (Cerbera odollam Gaertn.) could cause death to armyworm (Spodoptera litura (Fabricius) on 1.5% concentration of 55% showed effective on the armyworm. Increasing the dose is to be followed by increasing the effectiveness of mortality. The LC50 value is 1.51%. Increasingly concentration of seeds bintaro extract (Cerbera odollam Gaertn.) cause higher mortality of armyworm (Spodoptera litura (Fabricius). Keywords: Spodoptera litura (Fabricius), Cerbera odollam Gaertn. Seeds Extract, Mortality